Development of interactive book for kids: learn colors playing - Gurieva, Natalia; Aurora, Orozco Pérez (ХНУРЭ, 2017)
Nowadays, we live in a constant change, in the educational models and society, we see ourselves involved in a digital revolt that affects, not only in the industrial production but also sector of services, since this sector includes activities that involve the production of material goods such as education.
Keywords: book; color